Ventricular arrhythmias and sudden cardiac death caused by mitral valve prolapse: should we operate and when?. (3rd October 2022) - Cameron, J; Sutherland, N; Han, H C; Raman, J; Lim, H
Abstract: Background: Several autopsy and observational studies have investigated the link between mitral valve prolapse (MVP) and sudden cardiac death (SCD) due to the well accepted yet rare occurrence of complex ventricular arrhythmia (VA) in this cohort. Few studies however have investigated whether arrhythmia burden and more importantly SCD are reduced following surgical correction of MVP. Purpose: To investigate the impact of mitral valve surgery (MVS) (replacement or repair) on VA and SCD in patients with MVP. Methods: A systematic review of the current literature was conducted using an electronic search of the PubMed database in October 2021. Studies were included if subjects had undergone mitral valve (MV) repair or replacement with documented rates of arrythmias/SCD pre- and post-intervention. Small patient numbers in individual reports precluded formal meta-analysis and results were reported on a per study basis. Results: 19 identified studies (10 cohort studies, nine case studies) comprised 1322 patients with a pooled mean age of 63.4 years and 38.9% were female. 748 of the 1322 patients underwent MVS: 263 MV repair, 18 MV replacement (one with leaflet and papillary muscle excision), two MV repair with Maze procedure, 177 percutaneous transcatheter MV repair, 45 annuloplasty with or without valve repair, and in 243 cases the surgical method was not specified. Of the 10 included cohort studies, seven of the eight which investigated rates of VA post MVS concluded there was a significant reduction, while one reported the predisposition to arrythmia persisted after relieving the abnormal mechanical effects of non-ischaemic MR (75% due to MVP). One study reported a reduction in SCD post MVS. Each of the nine included case studies showed a reduction in VA post MVS. One study showed mitral annular disjunction (MAD) was independently associated with a higher risk of arrhythmic events, this link persisting with time dependent MVS although reduced compared to medical management. Conclusions: The underlying mechanisms for VA and SCD associated with MVP are not completely understood, and guidelines for the surgical correction of MVP based on arrhythmic and SCD risk are lacking. This systematic review illustrates a possible reduction in VA following MVS. Further identification of patients at risk of SCD, and potential use of risk stratification algorithms, would allow for consideration of earlier management and appropriate use of implantable cardioverter-defibrillators (ICD) placement / MVS with an expected survival benefit. Funding Acknowledgement: Type of funding sources: None.